Epidemiological Analysis of Fungal Infection Disease in Pediatric Population: Focus on Hospitalization from 2007 to 2022 in Veneto Region in Italy - Lorenzo Chiusaroli; Claudia Cozzolino; Silvia Cocchio; Mario Saia; Carlo Giaquinto; Daniele Donà; Vincenzo Baldo (Pathogens)
Fungal infections (FIs) are widespread globally, affecting both immunocompromised and immunocompetent children, with varying clinical implications based on age and comorbidities. In immunocompromised children, particularly those with hematologic oncological conditions, FI leads to substantially longer hospital stays and increased in-hospital mortality, with reported rates ranging from 15% to 20%. Our study aims to analyze the epidemiological trends of fungal infections in the pediatric population within a specific region of Italy. We extracted ICD-9 codes related to fungal infections from hospital discharge records (HDRs) in the pediatric population of Veneto, located in the north-east of Italy, between 2007 and 2022. We included all children admitted to the hospital with a primary or secondary diagnosis during admission for other reasons. Data were stratified based on age, year, ward of admission, and type of diagnosis. Patients older than eighteen and HDRs related to a second admission within thirty days from the previous admission were excluded. A total of 1433 diagnoses were analyzed during the period, with 241 (16.8%) as main diagnoses and 1192 (83.2%) as secondary diagnoses. The overall hospitalization rate was 1084 cases/100,000 (1.69 cases/100,000 as primary diagnosis and 8.95 cases/100,000 as secondary). The hospitalization rate stratified for age was 11,055 cases/100,000 among infants younger than 1 year, 8.48 cases/100,000 among those aged 1-4 years, and 4.4 cases/100,000 among children older than 5. The more frequent infection was Candida spp. (62.8%), followed by Aspergillus spp. (14.6%) and skin mycosis (9.5%). Overall, the pediatric in-hospital case fatality rate due to FI was 2.09%. Our study elucidated the overall experience of fungal infections in the pediatric population of the Veneto region in Italy. Specifically, we underscored a relatively stable hospitalization rate for fungal diseases and a noteworthy mortality rate.